Penggunaan Metode Dan Media Pembelajaran pada Muatan Pembelajaran IPAS di SDN Mojo 58 Kabupaten Sragen - Iguesti Retno Sri Mondo Arum, Abdul Rozaq Mubarok, Nindi Setyowati, Diah Wuriyani, Septyana Candra P (Elementary School and Education Journal, 2025)
This research aims to explore learning methods and media at SDN Mojo 58 Sragen, especially in science learning. Globalization brings major changes in the order of people's lives. These changes are driven by the increasing development of science and technology, which has an impact on various sectors of life, including the field of education. The design of learning media at this time must be based on student needs in accordance with learning needs. In this research, qualitative methods were used to explore teachers' experiences regarding the effectiveness of experimental methods and image media. Data was collected through in-depth interviews, literature studies and analyzed thematically. The research results show that the experimental method creates an interactive and student-centered learning atmosphere, and allows understanding of science concepts through direct learning experiences. The use of image media increases the attractiveness of learning and interaction between teachers and students. The combination of experimental methods and image media contributes positively to the quality of learning and student achievement. This research recommends the development of experimental methods and ongoing training for teachers to increase scientific literacy from an early age.